2014
DOI: 10.1111/hdi.12171
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis‐related headache

Abstract: Headache is one of the most frequently encountered neurological symptoms during hemodialysis. According to International Classification of Headache criteria dialysis-related headache was defined as the headache occurring during hemodialysis with no specific characteristic. It resolves spontaneously within 72 hours after the hemodialysis session ends. There are few studies in the literature investigating the clinical features of dialysis headache. The pathophysiology of hemodialysis-related headache is not know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Alessandri et al. (29) reported higher basal plasma concentrations of calcitonin gene-related peptide in patients (that is reported to be related to migraine pathophysiology (30,31), with dialysis-related headaches than in hemodialysis patients without headaches. They suggested that changes in the plasma concentrations of this peptide could contribute to the susceptibility of hemodialysis-related headache (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alessandri et al. (29) reported higher basal plasma concentrations of calcitonin gene-related peptide in patients (that is reported to be related to migraine pathophysiology (30,31), with dialysis-related headaches than in hemodialysis patients without headaches. They suggested that changes in the plasma concentrations of this peptide could contribute to the susceptibility of hemodialysis-related headache (32).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have been published regarding dialysis-related headache have been performed only in adult populations (19). We did not identify any published studies of headaches among pediatric or adolescent patients with chronic kidney disease or on hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Because this was a narrative review, we were unable to exclude the possibility of selection bias. We found just one narrative review about this theme, so we hope to contribute with the discussion about this important theme.…”
Section: Limitationsmentioning
confidence: 99%
“…DDS is not the only cause of hemodialysis-related headaches, defined by the International Classification of Headache as having no specific characteristics, occurring during dialysis and resolving within 72 hrs of the end of hemodialysis. Other etiologies include hypo- and hypertension, metabolic disturbances like hypoglycemia, hyper- and hyponatremia, hyperphosphatemia, uremia, caffeine deprivation, medication associated, stress and subdural hematomas 6,7. Often, the etiology is multifactorial and appropriate evaluation should be undertaken.…”
Section: Introductionmentioning
confidence: 99%